Environmental Impact Assessment Study for Shatt Al-Arab River Receiving Industrial Wastewater - Mohammed, Alya A.; Chalabi, Ahmed S. Al (Basrah Journal for Engineering Sciences, 2022)
Shatt Al-Arab river has been used as the raw material for the drinking water, irrigation and fish purposes in Basrah city. Concurrently, this river has been polluted by domestic, farming and industrial waste. Three main factories lie on the bank of Shatt Al-Arab river: Al-Hartha Paper Mill, Hartha Power Station and Al-Najibia Power Plant. All these consume water from the river and return their wastewater back to it. The aim of this study is to assess the water quality of Shatt Al-Arab river and its suitability for drinking, irrigation and aquatic life through physicochemical analysis temperature, pH, EC, Total Dissolve Solid (TDS), Cl − , Na + , K + , Ca +2 , Mg+2, HCO 3 total hardness, Biological Oxygen Demand (BOD5), Dissolved Oxygen (DO), Chemical Oxygen Demand (COD). BOD5 concentration near factories showed polluted water, unsafe and requiring costly treatment to use for drinking water. Sodium concentration is a key factor for irrigation, which represent by SAR and SSP. As SSP exceed 75.73 % in water near these factories, this could breakdown soil structure and can damage agriculture area. The high concentrations of BOD5 and COD could pose a threat to aquatic life and fishes. As Shatt Al-Arab river is used for different purpose, the result in this study showed polluted water near industrial areas. Therefore, it is recommended to have regular data on water quality for this river near these areas.